Quantitative Trait Analysis and Path Coefficient Modeling for Yield Optimization in Rice (Oryza sativa L.) Restorer Lines (International Journal of Agricultural Extension and Education, 2025)
This research focuses on the correlation and path coefficient analysis of 90 rice restorer lines (Oryza sativa L.) evaluated for 29 quantitative and qualitative traits to elucidate the key contributors to grain yield. The analysis revealed that traits such as panicle length, panicle index, productive tillers per plant, and harvest index exhibited a strong positive correlation with grain yield and exerted significant direct effects, making them reliable selection criteria for genetic improvement and hybrid breeding programs. In contrast, stem length displayed a significant negative correlation with grain yield at the genotypic level, while plant height showed negative direct effects, underscoring their limited relevance as indicators for yield enhancement. Furthermore, a negative association was observed between plant height, stem length, and several economic traits, including total tillers per plant, productive tillers per plant, 1000-grain weight, panicle index, and harvest index, at both genotypic and phenotypic levels. This association underscores the yield advantage of short-statured or dwarf genotypes, which are better suited for achieving higher grain yield. Notably, restorer lines with favourable traits, including total spikelets per panicle, fertile spikelets per panicle, and spikelet density percentage, were positively correlated with late maturity, indicating that late-maturing lines hold greater promise as superior restorers compared to early-maturing lines. Key traits identified for yield improvement include stem length, panicle length, panicle index, spikelet density percentage, productive tillers per plant, length-to-breadth ratio, harvest index, biological yield per plant, and decorticated grain width. These findings provide critical insights into the development of robust hybridization and breeding programs aimed at optimizing grain yield in rice.
Keywords: Correlation; Path Analysis; Association; Restorer lines; Direct effect; Hybridiza tion programme